2023
DOI: 10.3389/fpls.2023.1111001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular studies of rust on European aspen suggest an autochthonous relationship shaped by genotype

Abstract: Forests are at increasing risk from pathogen outbreak. Climate change for example enhance the risk of local disease outbreaks, and naturalization of exotic pathogens may follow human activities, warranting robust pest surveillance routines to support forest management. Melampsora pinitorqua (pine twisting rust) is of concern in Swedish forestry, and here we evaluate the use of visible rust scores (VRS) on its obligate summer host, European aspen (Populus tremula) as a tool for quantification of the pathogen. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Visual inspections included: plant height measured in centimeters (from the plant-soil intersection to the tip of the canopy); counting of Harmandiola galls; assessment of symptoms of Venturia sp. as wilted branches relative to the total number of branches per canopy; other biotic stress symptoms, such as leaf hypersensitive response (HR), abundance of eriophyid mite colonies, damage from chewing insects, and rust pustules (Melampsora pinitorqua [47,67]. Leaf damage symptoms were ranked on a 0-3 scale: 0 indicated no symptoms, 1 indicated low damage corresponding to symptoms on some leaves, 2 indicated moderate damage with symptoms on approximately half of the leaves, and 3 indicated a high level of damage with symptoms on more than half of the leaves.…”
Section: Nondestructive Phenotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…Visual inspections included: plant height measured in centimeters (from the plant-soil intersection to the tip of the canopy); counting of Harmandiola galls; assessment of symptoms of Venturia sp. as wilted branches relative to the total number of branches per canopy; other biotic stress symptoms, such as leaf hypersensitive response (HR), abundance of eriophyid mite colonies, damage from chewing insects, and rust pustules (Melampsora pinitorqua [47,67]. Leaf damage symptoms were ranked on a 0-3 scale: 0 indicated no symptoms, 1 indicated low damage corresponding to symptoms on some leaves, 2 indicated moderate damage with symptoms on approximately half of the leaves, and 3 indicated a high level of damage with symptoms on more than half of the leaves.…”
Section: Nondestructive Phenotypingmentioning
confidence: 99%
“…Hence, while our study suggested a negative impact of condensed tannins on the abundance of foliar-associated mycobiomes, it is premature to infer a simple relationship. Condensed tannins, for example, were reported to have a negative correlation with twig endophyte infection in poplars within a hybrid zone [95] as well as with the abundance of molecular markers of the biotrophic pathogen Melampsora pinitorqua [47], and the symptoms of necrotrophic pathogen Venturia infection in Populus tremula [66]. Moreover, in a review by Bhat et al (1998) [96], degradation primarily by lamentous fungi such as Aspergillus and Penicillium, along with yeasts, was found to degrade condensed tannins, potentially using them as substrate.…”
Section: Genotype and Environmental Effects On Aspen Leaf-associated ...mentioning
confidence: 99%
See 1 more Smart Citation